(untitled) (Al-Aasar, 2025)
This research study provides an analysis of various aspects of class struggle reflected in the short stories of Ahmed Nadim Qasmi. In his works, Qasmi has skillfully highlighted social inequalities and has brought to the forefront themes of human rights, justice, and equality. His stories primarily focus on the lives of marginalized individuals, such as the poor, workers, farmers, and lower classes, portraying their suffering and the injustices they face. In these stories, Qasmi paints a realistic and systematic picture of class differences, showing how these inequalities impact people’s lives. His narratives emphasize that social injustice is not just an individual issue but a collective social problem. His short stories, on one level, depict individual struggles, but on another level, they suggest that societal change and collective action are required to achieve social justice. This study affirms that Qasmi’s literature plays a crucial role in fostering awareness about class struggles and social justice, making it not only valuable to students of literature but also to the general reader. His stories illuminate social realities and encourage readers to reflect on the importance of justice and equality in their societies.